(untitled) (Journal of Educational Sciences, 2023)
Complex and contradictory processes of change in all spheres of public life in Kazakhstan impose special requirements on the quality of professional socialization of a young specialist and their professional education. The article is based on a comprehensive analysis of the problem of early adaptation of schoolchildren to vocational guidance in order to prepare competitive specialists who meet the requirements of the labor market. The results of a sociological study conducted among high school students in the regions of Kazakhstan are analyzed, differences in the attitudes of students in general education and specialized schools, and features of the professional choice of boys and girls are assessed. The purpose of the study is to analyze the impact of changes in the world, society, as well as the process of digitalization on the transformation of the main directions and trajectories of professional preferences of high school students. The main directions and ideas of the study are closely related to the reflection of ongoing changes in the field of secondary education in the context of the modernization of Kazakhstani society. The scientific significance of the work lies in the description of important priorities and values in the formation of professional preferences of high school students, and the practical significance in the implementation of important ideas reflected in state documents regarding the development of secondary education. The survey was attended by 558 respondents-high school students of Kazakhstan’s megacities: Astana, Almaty, Shymkent, as well as districts and rural areas of Almaty and Turkestan regions. The results obtained are valuable for the development of professional qualities of schoolchildren. Key words: professional preference, transformation, trajectory preferences, high school students, professionalism, professional orientation of schoolchildren.